Nutritive value of forages as affected by soil and climatic differences - Richardson, D.; Clary, F.G.; Banbury, Evans E.; Spaeth, C.W.; Erhart, A.B.; Arnett, D.W.; Boren, Fred W.; Perry, H.B. (Kansas State University. Agricultural Experiment Station, 2011)
Four previous tests (Kans. Agri. Expt. Sta. Bull. 507:7, 1967) at Colby, Garden City, Manhattan, and Mound Valley, using beef steers from the same herd and feeding the same feedstuffs, grown locally, produced differences in performance. What is the cause(s) of the differences? This test was designed as previous ones, except that all locations used the same feed, which was produced at Garden City. Sorghum silage was dehydrated and pelleted for easier transportation. The calves were wintered on the silage pellets and alfalfa hay. Silage pellets were gradually removed from the ration and sorghum grain added for finishing. Analyses of the feedstuffs are shown in table 12 . Feedlot performance and carcass data are shown in table 13. Results were more nearly uniform than for any previous year. The test is being repeated. An Atomic Absorption Spectrometer has been obtained and a complete mineral analysis of feedstuffs and water from each location is planned.
Keywords: Beef; Nutritive value; Soil; Climate; Sorghum silage; Alfalfa hay